Suspended Sediment Flow Routing by Discrete Linear Models - Kumar, Devendra; Rastogi, R A (Journal of Agricultural Engineering, 2006)
Discrete Linear sediment models were developed using sediment mobilized and direct sediment flow graphs of Chaukhutia watershed of the Ramganga reservoir catchment, India, and applied for sediment flow routing. The parameters of the models were estimated by Lagrangian method. The sediment graphs computed by these models compared with remarkable accuracy to the measured sediment graphs. The average values of integral square error, coefficient of efficiency and ratio of mean error to the mean observed output for four parameter sediment discharge model are 5.991 %, 97.183% and 0.0022 respectively. For three parameter sediment discharge model, the average value of relative error in estimated peak is 6.976%.